Spatially Filtered Vibration Control of Cylindrical Shells - H.S. Tzou; J.P. Zhong (Shock and Vibration)
Distributed actuators offer spatially distributed actuations and they are usually effective to multiple modes of a continuum. Spatially filtered distributed vibration controls of a laminated cylindrical shell and a piezoelectric shell are investigated, and their control effectivenesses are evaluated in this study. In general, there are two control actions, the in-plane membrane control forces and the counteracting control moments, induced by the distributed actuator in the laminated shell. There is only an in-plane circumferential control force in the piezoelectric shell. Analyses suggest that in either case the control actions are effective in odd natural modes and ineffective in even modes. Spatially filtered control effectiveness and active damping of both shells are studied.